In situ processing of fluorinated carbon—Lithium fluoride nanocomposites. (15th November 2018) - Schopf, Dimitri; Nielsen, Ulla Gro; Es-Souni, Mohammed
Abstract: Lithium fluoride (LiF) and fluoride additives in carbon-based materials are currently under research as electrode materials for energy storage applications. Herein we demonstrate a simple and novel method for the in situ fabrication of fluorinated carbon-LiF nanocomposites both as powder and as supported thin films. The starting solution of polyvinylidene fluoride (PVDF) and lithium nitrate (LiNO3 ) in N, N ‑Dimethylformamide is poured into a mould or applied to a thermally resistant substrate as a thin film. Pre-tempering and further pyrolysis at 550 °C yield LiF doped amorphous and fluorinated carbon (AC) powder or film. The precursor solution can be additionally modified with multi-walled carbon nanotubes (MWCNT) to yield porous AC-MWCNT-LiF-nanocomposites. Structural and morphological characterization (scanning electron and energy dispersive X-ray spectroscopy, X-ray diffraction as well as solid-state 7 Li magic angle spinning nuclear magnetic resonance spectroscopy) show a fine dispersion of faceted LiF-nanoparticles in the carbon matrix or decorating the MWCNTs. The formation mechanism involves the thermally activated reaction of Li-ions with the fluorine of the polymer during pyrolysis thus allowing an in situ nanocomposite to be obtained. Finally the electrochemical capacitance properties in a two-electrode set-up using LiNO3 in ethylene glycol as electrolyte are reported and discussed in comparison to LiF-free electrodes. Graphical abstract: Highlights: Fluorinated carbon - lithium fluoride powder and thin films are in situ fabricated. Polymer matrix is present before pyrolysis and fluorinated carbon after pyrolysis. Lithium nitrate particles with up to 1 μm size are observed before pyrolysis. Lithium fluoride particles with a mean size of 200 nm are detected after pyrolysis. Thermodynamic mechanisms and formation of intermediate products are discussed.